People i want to punch in the throat eaudiobook Competitive crafters, drop-off despots, and other suburban scourges. - Mann, Jen (Tantor Media, 2019)
A debut collection of witty, biting essays laced with a surprising warmth, from Jen Mann, the writer behind the popular blog People I Want to Punch in the Throat People I want to punch in the throat: ● anyone who feels the need to bling her washer and dryer ● humblebraggers ● people who treat their pets like children Jen Mann doesn't have a filter, which sometimes gets her in trouble with her neighbors, her fellow PTA moms, and that one woman who tried to sell her sex toys at a home shopping party. Known for her hilariously acerbic observations on her blog, People I Want to Punch in the Throat , Mann now brings her sharp wit to bear on suburban life, marriage, and motherhood in this laugh-out-loud collection of essays. From the politics of joining a play group, to the thrill of mothers' night out at the gun range, to the rewards of your most meaningful relationship (the one you have with your cleaning lady), nothing is sacred or off-limits. So the next time you find yourself wearing fuzzy bunny pajamas in the school carpool line or accidentally stuck at a coworker's swingers party, just think, What would Jen Mann do? Or better yet, buy her book.